Dose optimization of apomorphine sublingual film for treating "OFF" episodes in Parkinson's disease. (December 2021) - Olanow, C. Warren; Stocchi, Fabrizio; Peckham, Elizabeth L.; De Pandis, Maria Francesca; Sciarappa, Ken; Navia, Bradford
Abstract: Introduction: Apomorphine sublingual film is approved for the "on-demand" treatment of "OFF" episodes in Parkinson's disease (PD). Patients must undergo dose titration to determine their most effective and tolerable dose. We assessed whether higher doses than those that provide an initial "ON" response could yield more effective treatment. Methods: Patients with PD were assessed in the "OFF" state and the apomorphine sublingual film dose was titrated to a level that provided a tolerable "ON" response. The dose was then increased by up to two dose levels, if tolerated. A comparison in the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) Part III scores was made following administration of the dose that provided the initial "ON" response and following the higher dose. Treatment-emergent adverse events were also reported. Results: Thirty-five patients were titrated to higher apomorphine sublingual film doses than those that provided an initial "ON" response. A mean improvement in MDS-UPDRS Part III score was observed compared with the initial dose of 5.6 points ( P = 0.034), 4.4 points ( P = 0.009), and 3.7 points ( P = 0.018) at 30, 60, and 90 min postdose, respectively. Adverse events were mild or moderate and resolved with dose reduction without concomitant treatment. Conclusion: Higher doses of apomorphine sublingual film than those initially perceived to provide an "ON" response can be tolerated and provide additional improvement in motor function in many patients. Highlights: APL doses higher than associated with the initial "ON" response can further improve motor function. Findings support the clinical importance of APL dose optimization. Most patients can titrate APL without the need for antiemetics.